Pengaruh Work-Life Balance Dan Motivasi Kerja Terhadap Produktivitas Kerja Karyawan Pada PT. Telkom Regional VII Kota Makassar - Anugrah Nurjannah; Agung Widhi Kurniawan; Nurman; Amiruddin Tawe; Tenri Sayu Puspitaningsih Dipoatmojo (PT. Karya Inovatif Nusantara, 2025)
This study aims to analyze the influence of work-life balance and work motivation on employee productivity at PT. Telkom Regional VII Makassar. The research highlights the importance of balancing work and personal life, as well as work motivation, which significantly impacts employee productivity. A quantitative research method was employed, using questionnaires distributed to 60 employees. Data analysis was conducted using multiple linear regression to examine the simultaneous and partial effects of work-life balance and work motivation on employee productivity. The findings reveal that work-life balance, partially, does not significantly influence productivity (significance value 0.229 > 0.05). In contrast, work motivation has a positive and significant effect on productivity (significance value 0.000 < 0.05). These results underscore the critical role of work motivation in enhancing productivity. The findings are expected to guide company management in designing policies that foster productivity improvement